Networks-on-chip : from implementations to programming paradigms - Huang, Libo; Lai, Mingche; Ma, Sheng (Elsevier, 2015)
This book provides a thorough and bottom-up exploration of the whole NoC design space in a coherent and uniform fashion, from low-level router, buffer and topology implementations, to routing and flow control schemes, to co-optimizations of NoC and high-level programming paradigms. Its coherent and uniform format offers readers a clear, quick and efficient exploration of NoC design space. Topics include: novel and exciting research ideas, which encourage researchers to further delve into these topics; both engineering and theoretical contributions; detailed description of the router, buffer and topology implementations, comparisons and analysis that are of high engineering value